Implementation of e-Bupot Unifikasi for income tax article 23 at xyz apartment management agency - Aninditha Hafsari Putri; Lia Ekowati (Journal of Applied Sciences in Accounting, Finance, and Tax, 2023)
XYZ Apartment Management Agency, a non-profit organization, relies on collecting Management Fees from Resident Association members to fund the management and maintenance of Strata Title buildings. In the process of managing these properties, the agency avails various services, necessitating the deduction of Income Tax Article 23. This study aims to examine the procedures involved in calculating, paying, and reporting Income Tax Article 23 and the implementation of the e-Bupot Unifikasi system at XYZ Apartment Management Agency. Data collected covers the period from April 2022 to April 2023. A descriptive qualitative analysis method was employed, involving data collection from XYZ Apartment Management Agency, followed by an assessment of compliance with relevant tax regulations. This method was chosen because this research wants to describe the conditions that would be observed in the field more specifically, transparently and in depth. The study reveals that the current process of calculating, paying, and reporting Income Tax Article 23, using the e-Bupot Unifikasi system at XYZ Apartment Management Agency, does not align with the prevailing tax regulations. This non-compliance impacts in the imposition of administrative sanctions in the form of interest and fines on the XYZ Apartment Management Agency.